Finance and Development, September 1973. (Finance and Development; Finance and Development ;, 1973)
This paper focuses on the subject of development and income distribution, and suggests a method whereby economic development can be skewed in favor of the poor. The paper underscores that improvements in the distribution of income can be achieved by applying shadow cost significantly below money cost to determine the social cost of employing members of low-income groups and to use the social consolidation strategy in the choice of technology in the physical construction of projects. The application of this method would result in the more extensive use of labor instead of capital equipment.